The Effect of Service Quality and Price Fairness on Customer Loyalty with Customer Satisfaction as a Mediating Variable among Go-Ride Users in Padang City - Elena Aprilia; Whyosi Septrizola (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the effect of service quality, price fairness, and customer satisfaction as mediating variables on customer loyalty for Go-Ride users in Padang City. This type of research is quantitative with a causal design, using purposive sampling to select 150 respondents. Data were collected through a structured questionnaire using a Likert scale and analyzed with SmartPLS 4.1.1.4 software. The results showed that service quality and price fairness have a significant effect on customer satisfaction and customer loyalty. In addition, customer satisfaction mediates the relationship between service quality and price fairness with customer loyalty. This research has not been able to explain all aspects that affect customer satisfaction. Use a more complex model approach by adding other supporting factors to strengthen satisfaction levels.